1986
DOI: 10.1038/jcbfm.1986.72
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dexamethasone Pretreatment Aggravates Ischemic Neuronal Necrosis

Abstract: Summary: This study addresses the question of whether the cyclooxygenase inhibitors indomethacin and diclo fenac and the glucocorticosteroid dexamethasone ame liorate neuronal necrosis following cerebral ischemia. In addition, since these drugs inhibit the production of pros taglandins and depress phospholipase A2 activity, respec tively, the importance of free fatty acids (FFAs) on the development of ischemic neuronal damage was assessed. Neuronal damage was determined in the rat brain at I week following 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…In fact, studies about steroid-induced alterations of protein synthesis, dating back to the late seventies (Etgen et al, 1979) have so far supplied evidence for a role in several of these general cell processes: (1) The synthesis of GPDH was found to be increased by acute stress or corticosterone, with a delay of only 2 hr (Nichols et al, 1988(Nichols et al, , 1989Schlatter et al, 1990); (2) In hippocampal tissue glucocorticoids enhanced the amount of synapsin-1, a phosphoprotein which is involved in the control of neurotransmitter release (Nestler et al, 1981); the effect was apparent after 1 day, but reached a maximum after 7 days. By contrast, the mRNA for GAP43, another protein associated with transmitter release (Dekker et al, 1989), was not changed after 4 days corticosterone treatment (Nichols and Finch, 1991); t3~ Corticosteroid hormones may play a role in free radical formation, since they were shown to inhibit prostaglandin synthesis in the brain (Weidenfeld et at., 1987); however, lipid peroxidation was not altered (Koide et al. 1986).…”
Section: Metabolically Regulated Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, studies about steroid-induced alterations of protein synthesis, dating back to the late seventies (Etgen et al, 1979) have so far supplied evidence for a role in several of these general cell processes: (1) The synthesis of GPDH was found to be increased by acute stress or corticosterone, with a delay of only 2 hr (Nichols et al, 1988(Nichols et al, , 1989Schlatter et al, 1990); (2) In hippocampal tissue glucocorticoids enhanced the amount of synapsin-1, a phosphoprotein which is involved in the control of neurotransmitter release (Nestler et al, 1981); the effect was apparent after 1 day, but reached a maximum after 7 days. By contrast, the mRNA for GAP43, another protein associated with transmitter release (Dekker et al, 1989), was not changed after 4 days corticosterone treatment (Nichols and Finch, 1991); t3~ Corticosteroid hormones may play a role in free radical formation, since they were shown to inhibit prostaglandin synthesis in the brain (Weidenfeld et at., 1987); however, lipid peroxidation was not altered (Koide et al. 1986).…”
Section: Metabolically Regulated Characteristicsmentioning
confidence: 97%
“…calpains, endonucleases, phospholypase C, oxygen radical formation and severe acidosis eventually leads to delayed neuronal death (Siesjo and Bengtsson, 1989;Choi, 1988Choi, , 1990Meyer, 1989;Erecinska and Silver, 1989). Glucocorticoid hormones do not seem to reduce cellular metabolism to an extent that they are damaging by themselves, but they can clearly exacerbate the vulnerability to excitotoxins (Sapolsky, 1985), hypoxia/ischemia (Sapolsky and Pulsinelli, 1985;Koide et al, 1986) and hypoglycemia (Sapolsky, 1985) in hippocampal tissue. They do so regardless of their peripheral catabolic actions, since the aggrevation of induced lesions was also observed in isolated brain preparations Tombaugh et al, 1992).…”
Section: Metabolically Regulated Characteristicsmentioning
confidence: 99%
“…In humans, post-stroke cortisol concentrations are predictive of stroke outcome; high cortisol is associated with increased morbidity and mortality (10)(11)(12). Furthermore, experimental manipulations in rats that increase blood corticosterone concentrations during or after cerebral ischemia also increase infarct volume (13), whereas surgical or pharmacological suppression of corticosterone concentrations is neuroprotective (14,15). It has been proposed that rather than killing neurons directly, exposure to high concentrations of corticosteroids typically induces a physiological state that renders neurons more susceptible to subsequent neurologic insults (16).…”
mentioning
confidence: 99%
“…However, the authors stated that steroid administration might prevent death in patients harboring massive infarcts (Norris and Hachinski, 1986). In other studies, administration of glucocorticoids resulted in no or even detrimental effects on infarction size (Koide et al, 1986;Slivka and Murphy, 2001). Koide et al (1986) found that glucocorticoids administered intraperitoneally did not improve (acute pretreatment and post-treatment) but even aggravated (long-term pretreatment) infarction size in transient focal forebrain ischemia in rats.…”
Section: Discussionmentioning
confidence: 97%
“…They are used empirically to reduce inflammation and edema in the clinical setting, for example, after brain injury and in multiple sclerosis (Hoffmann et al, 2003;Rhodes, 2003). Interestingly, there are a few experimental and clinical studies available on the effects of glucocorticoids in acute cerebral ischemia reporting controversial results (Abraham et al, 2001;Akdemir et al, 2005;Bertorelli et al, 1998;de Courten-Myers et al, 1994;Koide et al, 1986;Lapchak et al, 2000;Limbourg et al, 2002;Norris and Hachinski, 1986;Patten et al, 1972;Slivka and Murphy, 2001;Tuor et al, 1993).…”
Section: Introductionmentioning
confidence: 99%